Cole's from Newcastle. Issue 1 (1st April 2013) - Franklin, Alex
Cheryl Cole – ex-judge of UK TV's The X Factor (Freemantle Media Ltd, 2004-present), ex-WAG of Chelsea and England footballer Ashley Cole, celebrated Geordie, sometime singer, fulltime 'style icon' and possessor of aspirational hair – represents a prime example of a hegemonic performance of femininity that is being normalized and presented as desirable by the mass media in the United Kingdom and beyond. This article examines the ambivalent relationship between class, power, regional identity and beauty that is Cole embodies.